The Effect of Jussiaea Octovalvis Weed Densities on the Growth and Yield of Several Introduced Vietnam Rice (Oryza Sativa) Varieties - Tu Ngoc Phan Thi; Ardi Ardi; Warnita Warnita (Universitas Andalas, 2020)
Rice is staple grain production that plays an important role in food security and the socio-economic value of agriculture in South East Asia countries. Among the factors that have negative effects on rice, weed is the major one. Its production constraint is directly seeded rice; besides, weed also affects rice growth and yield by competition about light, water, nutrient, space. Jussiaea octovalvis is a kind of weed in the field during rice growth to mature, which affects the growth and yield of rice but not significantly different based on this research. Treatments were arranged factorially in Randomized Block Design (RCBD) with two factors, 20 treatments (4 varieties, 5 of weed densities), and four replications, and each repetition used two pots for each treatment. As a result, the data showed the difference between the rate of growth and the yield of rice grain recovery products. Especially at data of LL 58 DAP showed significant difference (P=0.017), which the highest rate is 59.13 cm of V2; for harvest data showed that V3 is the best result, but it is also a sensitive one in the condition of weed densities impaction more than the others varieties (D0V3=620.5; D4V3=438). Besides, the measurement of W1000 of rice grain (30.96 g) and Wt per pot (20.01 g) of D0V3 is weight more than the other treatment; within D4V4 was obtained lowest of W1000 (19.26 g) and the lowest of Wt is D1V1 (5.25 g). Besides that, D2 and D4 are more effective on rice growth and yield, and it was non–significant. However, it is not the interaction between weed densities and varieties of rice.